PKM Penerapan Jam Tangan Mesjid dan Jam Tangan Alqur'an Portabel - Hendra Jaya; Bakhrani A. Rauf; Hafid Ridho Attamimi; Ahmad Risal; Lumu Taris (FKIP, Universitas Palangka Raya, 2024)
This community service focuses on the application of wearable technology in the form of Mosque Watches and Portable Al-Qur'an Watches, which are designed to support Muslim worship practices by increasing accessibility to information on prayer times and the text of the Al-Qur'an. This activity involved structured training attended by 25 participants, including mosque administrators and congregation, to ensure understanding and ability to utilize this device optimally. The results of the training showed a high level of participant satisfaction with aspects such as usefulness, quality, suitability for needs and ease of use of watches. Despite challenges such as limited digital literacy, the evaluation showed significant improvements in participants' ability to integrate this technology into their daily lives. The success of this program indicates that the integration of technology in religious practice has great potential to provide real benefits for society, and can be an inspiration for further developments in religious technology in various communities.